Development and validation of a high-performance liquid chromatography-ultraviolet spectrometry method for Ampicillin and its application in routine therapeutic drug monitoring of intensive care patients - Morath, Benedict; Schultes, Linda; Frey, Otto Roman; Röhr, Anka Christa; Christow, Hannes; Hoppe-Tichy, Torsten; Brinkmann, Alexander; Chiriac, Ute (Therapeutic drug monitoring, 2025)
Background: - Ampicillin/sulbactam, a combination of a β-lactam and β-lactamase inhibitor, is widely used in clinical settings. However, therapeutic drug monitoring (TDM) of ampicillin is not commonly performed, particularly in intensive care units (ICUs). The purpose of this study was to develop and validate a rapid and cost-effective high-performance liquid chromatography (HPLC)-ultraviolet spectrometry method to quantify ampicillin in human serum and evaluate its clinical application in ICU patients. - Methods: - Sample cleanup included a protein precipitation protocol, followed by chromatographic separation on a C18 reverse-phase HPLC column within 12.5 minutes using gradient elution of the mobile phase. The assay was validated according to the German Society of Toxicology and Forensic Chemistry criteria. Clinical applications involved the retrospective analysis of TDM data from ICU patients receiving continuous infusion of ampicillin/sulbactam, including the attainment of target ranges and individual predicted and observed pharmacokinetics. - Results: - The method was robust, with linear relations between the peak area responses and drug concentrations in the range of 2-128 mg/L. The coefficient of variation for precision and the bias for accuracy (both interday and intraday) were less than 10%. Clinical application revealed variable pharmacokinetics of ampicillin in ICU patients (clearance of 0.5-31.2 L/h). TDM-guided dose adjustments achieved good therapeutic drug exposure, with 92.9% of the samples being within the optimal (16-32 mg/L) or quasioptimal (8-48 mg/L) range. - Conclusions: - This method provides a practical solution for the routine TDM of ampicillin, facilitating individualized dosing strategies to ensure adequate therapeutic drug exposure. Given its simplicity, cost-effectiveness, and clinical relevance, HPLC-ultraviolet spectrometry holds promise for broad implementation in hospital pharmacies and clinical laboratories.
Gesehen am 12.08.2025